Cold ischemia with selective anterograde in situ pulmonary perfusion preserves gas exchange and mitochondrial homeostasis and curbs inflammation in an experimental model of donation after cardiac death. (29th July 2013) - Pottecher, Julien; Santelmo, Nicola; Noll, Eric; Charles, Anne‐Laure; Benahmed, Malika; Canuet, Matthieu; Frossard, Nelly; Namer, Izzie J.; Geny, Bernard; Massard, Gilbert; Diemunsch, Pierre
Summary The aim of this study was to assess the functional preservation of the lung graft with anterograde lung perfusion in a model of donation after cardiac death. Thirty minutes after cardiac arrest, in situ anterograde selective pulmonary cold perfusion was started in six swine. The alveolo‐capillary membrane was challenged at 3, 6, and 8 h with measurements of the mean pulmonary arterial pressure (mPAP), the pulmonary vascular resistance (PVR), the PaO2/FiO2 ratio, the transpulmonary oxygen output (tpVO2), and the transpulmonary CO2 clearance (tpCO2). Mitochondrial homeostasis was investigated by measuring maximal oxidative capacity (Vmax) and the coupling of phosphorylation to oxidation (ACR, acceptor control ratio) in lung biopsies. Inflammation and induction of primary immune response were assessed by measurement of tumor necrosis factor alpha (TNFα), interleukine‐6 (IL‐6) and receptor for advanced glycation endproducts (RAGE) in bronchoalveolar lavage fluid. Data were compared using repeated measures Anova. Pulmonary hemodynamics (mPAP: P = 0.69; PVR: P = 0.46), oxygenation (PaO2/FiO2: P = 0.56; tpVO2: P = 0.46), CO2 diffusion (tpCO2: P = 0.24), mitochondrial homeostasis (Vmax: P = 0.42; ACR: P = 0.8), and RAGE concentrations (P = 0.24) did not significantly change up to 8 h after cardiac arrest. TNFα and IL‐6 were undetectable. Unaffected pulmonary hemodynamics, sustained oxygen and carbon dioxide diffusion, preserved mitochondrial homeostasis, and lack of inflammation suggest a long‐lasting functional preservation of the graft with selective anterograde in situ pulmonary perfusion.